Ge0.98Si0.02 crystal grown by the travelling heating method using axial magnetic field and rotating crucible. (20th May 2008) - Jaber, T.J.; Labrie, D.; Saghir, M.Z.
A three-dimensional numerical simulation study was carried out for crystal growth of GeSi by the travelling heater method (THM). The effect of an axial magnetic field combined with crucible rotation was investigated. The effect of magnetic field intensity was studied first then the crucible rotation was added to the model. The full Navier-Stokes equations together with the energy, mass transport and continuity equations were numerically solved using the finite element technique. By increasing the magnetic field intensity, the intensity of the flow at the centre of the crucible decreased at a faster rate compared to the flow near the walls. This phenomenon created a stable and uniform silicon distribution in the horizontal plane and became relatively homocentric. The addition of a crucible rotation showed an improvement in the suppression of the flow intensity.